2015
DOI: 10.1039/c5ra19331a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterisation of MOF/ionic liquid/chitosan mixed matrix membranes for CO2/N2 separation

Abstract: The CO2 permeability and CO2/N2 selectivity of IL–CS membranes is improved by adding nano-HKUST-1 and ZIF-8, and predicted accurately by Maxwell-derived model as a function of interfacial contact, crystallinity and pore blockage with temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(73 citation statements)
references
References 70 publications
(108 reference statements)
2
71
0
Order By: Relevance
“…b, the HKUST‐1/IL‐CS‐based membranes are observed. The HKUST‐1 nanoparticles were found homogeneously dispersed all along the perimeter of the outer layer of the CHF membrane, and very well dispersed in the selective layer of the composite flat membrane, as the Cu from HKUST‐1 was homogeneously distributed throughout the dense IL‐CS unsupported membrane . As to the zeolite A/PTMSP‐based membranes (Fig.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…b, the HKUST‐1/IL‐CS‐based membranes are observed. The HKUST‐1 nanoparticles were found homogeneously dispersed all along the perimeter of the outer layer of the CHF membrane, and very well dispersed in the selective layer of the composite flat membrane, as the Cu from HKUST‐1 was homogeneously distributed throughout the dense IL‐CS unsupported membrane . As to the zeolite A/PTMSP‐based membranes (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…The permeation data in Tab. also demonstrates that one coating is insufficient to achieve a membrane as selective as the dense homogeneous unsupported IL‐CS hybrid membrane , . The thickness of the ZIF‐8/6FDA‐DAM layer coated on 6FDA‐DAM HF membrane presented by Zhang et al has to be at least 7–12 µm to assure adhesion and avoid defects.…”
Section: Resultsmentioning
confidence: 99%
“…[8][9] IL-MOF combinations have been considered recently in the gas separation field. [10][11][12][13][14][15][16] For instance, Chen et al 17 incorporated IRMOF-1 composite and reported a CO 2 /N 2 selectivity of 70 at ambient conditions. To understand the effect of different types of ILs on the separation performances of IL-MOF systems, ILs with the same cations but different anions were studied.…”
Section: Introductionmentioning
confidence: 97%
“…In order to form successful MMMs, one must maintain flexibility during membrane formation (the use of high temperatures) and interaction between polymer and sieve phase (chemical coupling) [39,51,52].…”
Section: Pi-thementioning
confidence: 99%